Morphological Heterogeneity and Ethnic Patterning of Anthropometric Traits in Ethiopian Inter-Scholastic Athletes - Dr. Harish Kumar; Degele Shomogro; Dr. Pushpdeep Singh (Recent Trends in Sports, 2026)
Introduction: Anthropometric characteristics such as body size, proportions, and composition are fundamental determinants of morphological suitability for sport. Ethiopia’s significant ethnic diversity suggests potential variability in these traits; however, systematic data on anthropometric differences among adolescent athletes from different ethnic and demographic backgrounds remain limited. Understanding these variations is critical for talent identification and sports specialization at the school level. Methods: A cross-sectional study was conducted among inter-scholastic athletes representing multiple Ethiopian ethnic groups. Standardized anthropometric assessments were performed following ISAK and CDC protocols. Measurements included body mass, stature, BMI, limb lengths, segmental girths, and selected skinfold thicknesses. Instruments were calibrated prior to testing, and all measurements were taken by a trained assessor to ensure reliability. Data were analyzed to identify ethnic and demographic variations in morphological characteristics. Results: The analysis revealed notable differences across ethnic groups in key anthropometric variables, including limb segment lengths, girth measurements, and overall body composition. Some ethnic groups exhibited longer lower-limb segments, lower BMI profiles, and distinct proportionality patterns that may offer advantageous morphology for endurance or speed-based sports. Demographic factors, including regional background, also contributed to variations in body size and proportions. Conclusion: Distinct anthropometric patterns exist among inter-scholastic athletes from different Ethiopian ethnic and demographic groups. These variations highlight the influence of ethnic background on body morphology and underscore the value of anthropometric profiling in youth sport development and talent identification. Establishing comprehensive anthropometric data across Ethiopia’s diverse populations can support more effective athlete selection, training planning, and long-term sport development strategies.
Keywords: Anthropometric Variables; Body mass index; Ethiopian Athletes; Limb Circumference; Waist Circumference